Children of men [videorecording (DVD)] - Cuarón, Alfonso; Owen, Clive; Moore, Julianne; Caine, Michael; James, P. D. (Universal Pictures, 2007)
London, 2027. Humanity has become infertile and no child has been born for 18 years. Science is at loss to explain the reason. Immigration is a crime and regugees are caged like animals. African and East European societies have collapsed and their dwindling populations are migrating toward England and other wealthy nations. Torn apart by nuclear fallout, rampant terrorism and political rebellion. In this climate of nationalistic violence, a London peace activist turned bureaucrat Theo Faron, joins forces with Julian, his revolutionary ex-wife, in order to save mankind by protecting a woman who has mysteriously became pregnant. These three set out on a desperate struggle to deliver the world's only pregnant woman to the Human Project with hope that they can discover the cure for global infertility. As they carefully navigate between the battling forces of military police and a pro-immigration insurgency this small group must endure a death-defying ordeal of urban warfare.